2022
DOI: 10.22161/ijebm.6.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Financial crisis: Non-monetary factors influencing Employee performance at banking sectors

Abstract: Money and credit fluctuations, financial crises, and governmental responses have come into the spotlight as a result of the crisis that lasted from 2014 to 2018. The primary objective of this study was to investigate the non-financial elements that have an effect on employee performance in the Kurdistan region of Iraq in general and in Erbil in particular. In spite of this, the researcher came up with five assumptions about study that needed to be evaluated and quantified in order to assess how well employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In this research as a part of the qualitative research, the focus group interviewing is used to obtain adequate information from the participants and to get to their perception in terms of their notion to assess the delivery of the quality service and the techniques of recovery approach after showing the service failure. The use of the interview method is to gain research-relevant information from the interviewee, it is evident that the result of the interview is to be subject for achieving the research objectives of describing, predicting or explaining the phenomenon (Hamza et al, (2022);Sharifi & Sultan, 2021;Cohen &Manion, 2007 in Dilshad R andLatif M, 2013). To achieve the objective of this research randomly, six five Star hotel guests and two employees from two different hotels have been chosen from a variety of age backgrounds, gender, and professions in Erbil.…”
Section: Methodsmentioning
confidence: 99%
“…In this research as a part of the qualitative research, the focus group interviewing is used to obtain adequate information from the participants and to get to their perception in terms of their notion to assess the delivery of the quality service and the techniques of recovery approach after showing the service failure. The use of the interview method is to gain research-relevant information from the interviewee, it is evident that the result of the interview is to be subject for achieving the research objectives of describing, predicting or explaining the phenomenon (Hamza et al, (2022);Sharifi & Sultan, 2021;Cohen &Manion, 2007 in Dilshad R andLatif M, 2013). To achieve the objective of this research randomly, six five Star hotel guests and two employees from two different hotels have been chosen from a variety of age backgrounds, gender, and professions in Erbil.…”
Section: Methodsmentioning
confidence: 99%
“…The capital structure is heavily influenced by the size of the organization, which is given high priority . As a result, larger institutions benefit from greater earnings diversification and less volatile annual earnings, which in turn reduces the financial liabilities associated with them (Hamza et al, 2022). This makes it easier for them to tolerate a high proportion of debt in oversized businesses with a smaller capital structure (Abdalla .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hypothesis three: There is a significant relationship between floatation as element of capital structure with firm Profitability. As it can be seen in table (12), the correlation analysis between floatation as a skill of self-leadership as a tangible resource to measure its influence on firm Profitability in firms in Kurdistan region of Iraq. The finding revealed that the value of Pearson correlation (r= .672 **, p<0.01), this indicated that there is positive and strong correlation between floatation as self leadership skill and firm Profitability.…”
Section: Third Research Hypothesismentioning
confidence: 99%
“…given time, it is quite probable that you are engaging in some form of stage shopping (Hamza et al, 2022). You are thinking about the many different kinds of things that you require or will eventually buy, and you are attempting to identify the most straightforward options available at the most straightforward price, in addition to determining when and how you will acquire these things, and you are checking some products that you have already purchased.…”
Section: Journal Of Humanities and Education Development (Jhed) 4(6)-...mentioning
confidence: 99%